2020
DOI: 10.2196/18555
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual Global E-Learning Pediatric Endocrinology and Diabetes Curriculum for Front Line Health Care Providers in Resource-Limited Countries: Development Study

Abstract: Background Electronic learning (e-learning) is a widely accessible, low-cost option for learning remotely in various settings that allows interaction between an instructor and a learner. Objective We describe the development of a free and globally accessible multilingual e-learning module that provides education material on topics in pediatric endocrinology and diabetes and that is intended for first-line physicians and health workers but also trainees … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Urstad et al [21] concluded that when sharing e-learning resources across countries, an adaptation and translation process that includes a multicultural and multidisciplinary perspective is needed. In view of this concern, authors from all over the world have been invited to contribute to the content of the ESPE e-Learning website, and, in particular, the content of the module “Health Care in Resource Limited Setting” was written by authors from low- and middle-income countries [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urstad et al [21] concluded that when sharing e-learning resources across countries, an adaptation and translation process that includes a multicultural and multidisciplinary perspective is needed. In view of this concern, authors from all over the world have been invited to contribute to the content of the ESPE e-Learning website, and, in particular, the content of the module “Health Care in Resource Limited Setting” was written by authors from low- and middle-income countries [5].…”
Section: Discussionmentioning
confidence: 99%
“…The module comprises 16 chapters and 24 interactive problem-solving case studies (vignettes) exemplifying clinical issues and pitfalls, with specific attention to the 3 levels of medical health care in resource-limited settings (Table 1). The entire content has been translated by native French-, Spanish-, Swahili-, and Chinese-speaking colleagues into their respective languages [5]. This module has been well received, particularly in targeted parts of the world as shown in Figure 3.…”
Section: Applicationsmentioning
confidence: 99%
“…[44][45][46] Descriptive studies and expert opinion Most descriptive studies focused on the application of either EL or EC for targeting specific health conditions such as infectious diseases (mostly HIV and TBC), 47-55 maternal and child care, 56-64 and pediatrics (Supplementary Tables S1F and S1G). [65][66][67][68] Additional targeted health conditions where EL or EC has been used include cardiology, 41,69 neurology, 44 dermatology, 70,71 and oncology. 72,73 Our search did not find studies related to other relevant types of health conditions in this area according to Winters, 14 such as mental health, trauma, and disabilities.…”
Section: Nonrandomized Trialsmentioning
confidence: 99%
“…2). The ESPE elearning for resource-limited countries (RLC) modules were further developed and specifically targeted for frontline health-care providers, medical doctors, and special-ists in RLC [7]. The RLC modules provide an up-to-date globally accessible multilingual curriculum in 4 other languages: French, Spanish, Swahili, and Chinese, enabling access to non-English speaking health-care professionals and students.…”
Section: E-learning Platformmentioning
confidence: 99%